Manners Towards the Right to Privacy of Family Members: An Analysis of Al Azhar's Perspective on Surah An-Nur verses 58-59 - Ummi Muffidhah; Yeti Dahliana (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
Surah An-Nur verses 58-59 discusses manners and ethics in the household, especially related to the right to privacy of fellow family members and personal boundaries. This research aims to analyze in depth and interpret the meaning contained in Surah An-Nur verses 58-59, focusing on the perspective of Al-Azhar interpretation by Buya Hamka while looking at the historical and social context of the descent of these verses, as well as exploring how they are applied in the context of modern life. The research method used is a literature study with a thematic interpretation approach (maudhu'i). The results of the study show that the interpretation of Tafsir Al-Azhar Surah An-Nur verses 58-59 emphasizes the values of character education, politeness, and the importance of maintaining the right to privacy of family members in the home, where in this modern era, the concept of privacy in the home also intersects with issues such as early puberty, household ethics and the right to privacy in the wider community. Analysis of the interpretation of Al-Azhar and also the opinion of Buya Hamka is expected to influence a deeper mindset and understanding for a person regarding social ethics and the right to privacy in a social society.